2019
DOI: 10.1088/1742-6596/1363/1/012081
|View full text |Cite
|
Sign up to set email alerts
|

Decision Support System for Deciding Eligible Journals to be Published in Majalah Kedokteran Nusantara Using the Fuzzy Logic Method

Abstract: The decision to determine whether or not a journal to be published in Majalah Kedokteran Nusantara can be decided by using the Decision Support System with certain methods. One of methods used is fuzzy logic method and is applied to the Microsoft Visual Basic programming language. From the results of the research, the first step that must be done in determining a journal is published was to identify the problem and to determine how to evaluate the quality of the journal which is done by calculating the paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…MATLAB implementation to find out precise and more precise results. Making Conclusions From all stages of research that have been carried out in the form of data that has been processed by the Sugeno method [9].…”
Section: Figure 1 Research Designmentioning
confidence: 99%
“…MATLAB implementation to find out precise and more precise results. Making Conclusions From all stages of research that have been carried out in the form of data that has been processed by the Sugeno method [9].…”
Section: Figure 1 Research Designmentioning
confidence: 99%
“…Mie Akwang. Several previous studies that used fuzzy logic methods in solving noodle production problems, including [6], [7] in his research concluded that fuzzy logic can increase the efficiency and effectiveness of production figures and sales figures are more stable and can reduce losses caused by the tendency of differences in production and sales figures. noodle sales assisted using the Fuzzy Logic application.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by [11], it was concluded that the Fuzzy Sugeno method is better than the fuzzy Tsukamoto method in calculating the prediction of ordering Jordan bread because the Sugeno method has an average prediction accuracy rate of 0.0176% while the truth level the average prediction of the tsukamoto method is 0.504288%. Research conducted by [12] concluded that fuzzy logic with the Sugeno method can be used to help residents decide the best price for choosing the land used in the construction of minimarkets and be able to assess near or far distances that can determine the selling price of the land [13].…”
Section: Introductionmentioning
confidence: 99%